Evaluation of remote radiologist-interpreted point-of-care ultrasound for suspected dengue patients in a primary health care facility in Colombia - Lyda Osorio; Iñigo Prieto; Daniela Zuluaga; Deliana Ropero; Neelesh Dewan; Jonathan D. Kirsch (BMC, 2023)
Abstract Background Early identification of plasma leakage may guide treatment decisions in dengue patients. This study evaluated the value of point-of-care ultrasound (POCUS) to detect plasma leakage and predict hospitalization or referral to a higher level of care in suspected dengue patients under routine conditions at a primary care facility in Colombia. Methods We conducted a cohort study between April 2019 and March 2020 in a primary care hospital in Cali, Colombia. We prospectively included and followed 178 patients who were at least 2 years old with fever of less than 10 days and clinician-suspected dengue. A trained general practitioner performed a standardized POCUS protocol. Images were quality-rated and overread by an expert radiologist, and her results and those of the general practitioner were compared using the Kappa index. Logistic regression was used to identify factors associated with plasma leakage at enrollment and explore its prognostic value regarding hospital admission or referral to a higher level of care. Results Half (49.6%) POCUS images were of suitable quality to be interpreted. The proportion of plasma leakage reported by the radiologist was 85.1% (95% CI: 78.6-90.2%) and 47.2% by the study physician (Kappa = 0.25, 95% CI: 0.15-0.35). The most frequent ultrasound findings were ascites (hepatorenal 87.2%, splenorenal 64%, or pelvic 21.8%) and gallbladder wall thickening (10.5%). Plasma leakage was higher in subjects with thrombocytopenia (aOR = 4, 95% CI: 1.3-12.1) and lower in patients 30-59 years old (aOR = 0.1, 95% CI: 0.0-0.4) than in those 18 years old or younger. POCUS evidence of plasma leakage (aOR = 8.2, 95% CI: 2.2-29.9), thrombocytopenia (aOR = 6.3, 95% CI: 2.4-16.0) and pulse pressure (aOR = 1.1, 95% CI: 1.07-1.2) were associated with hospital admission or referral to a higher level of care. Conclusions Ultrasound is useful to detect plasma leakage in primary care and, challenges remain to guarantee high-quality images and diagnostic accuracy, for which a standardized dengue POCUS protocol and training program is needed. Graphical Abstract